An Examination of the Logistics Infrastructure's Impact on the Economic Growth of ASEAN - Parianom, Raden; ., Desmintari; Utami, Kery (KnE Social Sciences, 2024)
Despite the substantial economic potential, ASEAN faces challenges in meeting its infrastructure investment needs, resulting in suboptimal logistics performance for several countries. This study proposes an analysis of the contribution of logistics infrastructure and infrastructure investment in ASEAN countries to the overall economic growth of ASEAN. This study also aims to provide valuable insights for formulating effective policies that promote regional connectivity and accelerate economic integration in the ASEAN region. This study employs a fixed effect model with panel data from eight ASEAN nations (Cambodia, Indonesia, Malaysia, Myanmar, the Philippines, Thailand, Singapore, and Vietnam) gathered between 2021 and 2022. The results show that ASEAN countries’ logistics infrastructure is yet to affect ASEAN economic growth optimally. However, ASEAN countries’ domestic infrastructure investment significantly and negatively affects ASEAN economic growth. ASEAN governments must prioritize and actively develop logistics infrastructure, both nationally and regionally, to help develop regional linkages and promote sustainable economic growth rates. They should also intensify coordination efforts, optimize regional financial integration, identify alternative funding sources, and assess regulations restricting private sector participation to maximize private sector investments in infrastructure development, including public-private partnership (PPP). Keywords: ASEAN, economic growth, fixed effect, infrastructure investment, logistic infrastructure